Assessing azithromycin's ecological toll: Unveiling multifaceted impacts on Poecilia reticulata THROUGH biomarker analysis - Marinsek, Gabriela Pustiglione; Tagliamento, Manuela Agullo [UNESP]; Oliveira, Isabelly Cristina Correia dos Santos [UNESP]; Capaldo, Anna; Gusso-Choueri, Paloma Kachel; Ribeiro, Caio César [UNESP]; Feitosa, Ana Carolina Cruz [UNESP]; Abessa, Denis Moledo de Souza [UNESP]; Oliveira, Marcos Antônio [UNESP]; Mari, Renata de Britto [UNESP] (Elsevier, 2025)
This study investigates the impact of environmentally relevant concentrations of azithromycin on Poecilia reticulata, through biomarkers at different levels. To this end, the somatic indexes of P. reticulata were evaluated, and liver and gill samples were collected and analyzed for biochemical and histopathological alterations. Azithromycin caused significant effects in P. reticulata, such as increased hepatosomatic index, altered redox responses, particularly in gills, indicating oxidative stress, and notable tissue damage in the liver and gills in a dose-dependent response manner. Principal Component Analysis highlighted differences between control and exposed groups, demonstrating the azithromycin's influence on organismal homeostasis. This research underscores the importance of understanding azithromycin action in nontarget organisms of aquatic environments.
Keywords: Antibiotic; Biochemical biomarkers; Emerging contaminants; Fish; Gills; Histopathology; Liver